Development of Teacher-Centered Learning Model with Prophetic Values - Sari, Nuraeni Nanda; Ermawati, Imas Ratna (Jurnal Pendidikan MIPA, 2022)
In practice, the blended learning method still applies the Teacher Centered Learning (TCL) model because teachers have a role to control the learning condition remains conducive. This research aims to develop a Teacher Centered Learning model through prophetic integration in blended learning. The research was conducted at SMA Negeri 14 Bekasi and SMA Negeri 17 Bekasi with Research and Development method. The results showed that the average value of the usefulness of the TCL model was 82.48% (good) with the results of Shidiq (not imitating answers, not copying others work, daring to provide accurate information, and daring to give arguments) and Amanah (doing tasks well, playing an active role, and doing something that is ordered). Thus, the development of the Teacher Centered Learning model is feasible to apply in blended learning teaching. Keywords: teacher-centered learning model, prophetic values, research and development. DOI: http://dx.doi.org/10.23960/jpmipa/v23i4.pp1790-1801